DERIVATIONAL SUFFIXES IN THE RETURN OF SHERLOCK HOLMES NOVEL: A MORPHOLOGICAL ANALYSIS - Ni Made Citra Wahyu Ningsih; Ni Putu Cahyani Putri Utami (Universitas Warmadewa, 2024)
In the context of a language must have their respective positions as an effort to classify sentences in several positions. The main purpose of the classification of positions is to provide direction and explanation regarding the meaning of a sentence when it is collaborated with others sentences. Words that have initial positions as nouns or adjectives to verbs and adverbs will be in their position if they get an addition at the end of the word according to their context and use. The purpose of this paper is to analyze the reasons for the change of each basic word and to find out the context of the changes made so that the reader has a deep understanding when reading the novel